Analisis Kelayakan Pengembangan Bisnis Hatchery Pada Peternakan Unggas Itik Pedaging Berkah Mandiri Farm Lamongan - M. Irsyad Ulum Muddin; Daniel Kurniawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the feasibility of developing a hatchery business at Berkah Mandiri Farm, a meat duck farming enterprise in Lamongan Regency. The evaluation focuses on five key aspects: legal, market, technical, human resources (HR), and financial, to determine the potential sustainability of the hatchery business. This research adopts a qualitative approach with axial coding techniques in data analysis to identify relationships between variables. The findings reveal that the hatchery business has a significant market opportunity due to the increasing demand for Day Old Ducks (DOD) in the region. Technically, modern hatchery technology can enhance production efficiency and DOD quality. The HR aspect emphasizes the importance of workforce training to support business sustainability. Financial analysis indicates that an investment of IDR 269,700,000 results in a Payback Period of 14.16 months, with a positive Net Present Value (NPV) and a competitive Internal Rate of Return (IRR), confirming the project's feasibility. Considering these factors, this study concludes that the establishment of a hatchery in Lamongan Regency is both economically and strategically viable and can contribute to the independence of DOD supply for local farmers. Additionally, this study provides strategic recommendations for the sustainable and competitive management of the hatchery business in the national poultry market.